King of the jungle - Yadok, Bizuum (Fiction (Ibadan, Nigeria), 2014)
In King of the Jungle, the bouts of ethno-religious violence in Jos are fused with the heartbreaking story of two brothers who go through life unaware of each other's existence. Carefully crafted with local colour which evokes memories of pre-2001 Jos, Bizuum Yadok's first novel weaves humour, urban realism, tragedy and redemption.